A high throughput computational investigation of the solid solution mechanisms of actinides and lanthanides in zirconolite. Issue 41 (20th July 2021) - Dimosthenous, Stavrina; Handley, Christopher M.; Blackburn, Lewis R.; Freeman, Colin L.; Hyatt, Neil C.
Abstract : Computer simulations identify the energetics of different defects in the zirconolite system highlighting the different chemistries and sizes. Abstract : In this work, we perform a theoretical investigation of the actinide and lanthanide solid solution mechanisms of zirconolite-2M, prototypically CaZrTi2 O7, as a candidate immobilisation matrix for plutonium. Solid solution energies were calculated using static atomistic simulations by means of the General Utility Lattice Program, for formulations of relevance to ceramic wasteform deployment, with substitution on the Ca 2+ and Zr 4+ sites by Ce 4+, Pu 4+, Th 4+, and U 4+, and appropriate charge balance by substitution of Al 3+ or Fe 3+ on Ti 4+ sites. In simple solid solutions involving substitution on the Zr 4+ site, we found that whereas substitution of Ce 4+, U 4+ and Pu 4+ were energetically favoured, substitution of Th 4+ was not energetically favoured. For more complex solid solutions involving Ce 4+, Pu 4+, Th 4+, and U 4+ substitution on the Ca 2+ site, we found the most energetically favoured scheme involved co-substitution of Al 3+ or Fe 3+ on the five-fold co-ordinate Ti 4+ site in the zirconolite-2M structure. Comparison of these computational data with experimental evidence, where available, demonstrated broad agreement. Consequently, this study provides useful insight into formulation design and the efficacy of Ce 4+, U 4+ and Th 4+ as Pu 4+ surrogates in zirconolite-2M ceramic wasteforms for plutonium disposition.